ANALISIS PERILAKU DISRUPTIF SISWA DALAM PEMBELAJARAN DI SEKOLAH DASAR - Salsabila Rahmani, Balqis; Siti Nurwahidah, Lina; Nuriyanti , Risma (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Disruptive behavior in elementary school students is a persistent problem that can hinder the effectiveness of classroom learning and disrupt the learning process of other students. This article presents the results of a qualitative study using a case study approach regarding disruptive behavior exhibited by a third-grade student at SDIT Darul Abror during the learning process. Using a qualitative case study approach, research data were obtained through classroom observations, interviews with homeroom teachers and parents, and documentation reviews conducted at SD IT Garut. The results are explained using scientific theories on child behavior and psychosocial development, then compared with the results of previous studies. The research findings indicate that disruptive behavior in students appears in the form of lack of focus during learning, verbally interrupting friends, and disobeying teacher instructions. This behavior is influenced by internal factors such as temperament and self-regulation skills, as well as external factors such as family parenting styles, teacher approaches, and interactions with peers. These findings provide practical implications for teachers, schools, and parents in creating a more conducive learning environment and supporting students' social-emotional development.